Blood cross-matching using gel card technique compared to conventional tube technique: A diagnostic evaluation study - Aditi Pandey; Sonal Chandrakar; Roshan Lal; Kajal Chandrakar (MRIMS Journal of Health Sciences, 2025)
Background: Conventional tube technique (CTT) is the most commonly used method for blood cross-matching in India. The gel card technique is the latest technique emerged and due to its accurate results, it is considered a method of choice for cross-matching. Objective: The objective of the study was to compare blood cross-matching using the gel card technique compared to CTT with and without anti-human globulin (AHG). Materials and Methods: A diagnostic evaluation study was conducted on 1500 blood samples. Patients’ blood samples were sent to the blood bank for routine cross-matching procedures. Both tube and gel techniques were used for Coombs cross-matching and their results were compared and analyzed. Results: In our study, males were slightly more than females. The most common indication for blood transfusion was associated with medical conditions (28.4%). The gel card technique was as accurate as CTT with AHG. It was 100% sensitive and specific. At the same, the positive predictive value (PPV) and negative predictive value (NPV) are also 100%. The CTT sensitivity was 98.99% and it was 100% specific. The PPV was also 100% but the NPV was only 37.5% which means that the false-positive rate was very high with CTT compared to CTT with AHG. Because CTT without AHG in present study showed more false positive results as compared to gel matrix. The average time required for a single compatibility test by gel card method was 25 ± 3.5 min, while that for CTT with AHG was 90 ± 4.9 min (indirect antiglobulin test [IAT]) and 30 ± 3.8 min if IAT was not done. Thus, even though CTT with AHG was equally effective as that of the gel card method, but time taken was significantly more (P < 0.05). Conclusion: The gel technique has definite advantages over the tube technique because of being able to give more accurate results, less chances of false-positive and false-negative results, interpretation of results more objective consistent and reproducible, and its shorter duration for cross-matching. However, in developing countries like India, the gel technique if applied widely, costs factor would come down and could be considered a better alternative to CTT to ensure successful transfusion.